Risk Factors of Malnutrition among Under Five Children Admitted in a Nutritional Rehabilitation Center in Lalitpur - Sharma, Pratima; Onta, Mandira (Journal of Nursing Education of Nepal, 2023)
Malnutrition not only posses immediate threat to child’s health and life but also entails long  term impact to physical and mental growth. Study Entitled “Risk Factors of Malnutrition  among Under Five Children Admitted in a Nutritional Rehabilitation Center in Lalitpur”  was conducted to assess the risk factors of malnutrition among under 5 children using case  control design. Cases included malnourished under five children admitted in Nutritional  Rehabilitation Center (NRC) Lalitpur and controls included well nourished under five children  attending Well Baby Clinic of Tribhuvan University, Teaching Hospital (TUTH), Maharajgunj  in the ratio of 1:2. Altogether 136 samples were selected by non-probability purposive sampling  technique. Interview schedule with semi-structured questionnaire was used for data collection.  The findings were analyzed using descriptive statistic (mean, standard deviation) and  inferential statistics (multiple logistic regression) for identifying the strength of association. Findings of the study shows that ethnicity (Adjusted Odds Ratio [AOR]=2.462), birth  weight (AOR=7.683), birth order (AOR=5.906), number of family members (AOR=2.8),  father’s occupation (AOR=6.539), economic status (AOR=2.927), Vitamin A (AOR=11.592),  washing hand by mother before feeding the child (AOR=40.422), frequency of feeding the  child (AOR=24.178), use of purified drinking water (AOR=5.040), method of waste disposal  (AOR=16.892), other illness (AOR=5.38), place of first health seeking (AOR=17.435) and  previous hospitalization (AOR=2.273) were significantly associated with malnutrition. Most of  these risk factors if identified timely can be prevented and controlled by appropriate intervention.
Keywords: Malnutrition; Under Five Children